University of Florida Potato Variety Spotlight: Red LaSoda - Lincoln Zotarelli; Doug Gergela; Chad M. Hutchinson; David Dinkins; Edsel Redden (EDIS)
Red LaSoda is the red-skinned fresh-market potato standard for Florida. It was observed in 1949 as a deep red mutant of LaSoda in the Louisiana potato breeding program. It has been in trials over many seasons and at many locations in Florida including university and grower sites. Production and quality results provided in this 4-page fact sheet are summarized from the red-skinned fresh-market trials conducted by the University of Florida over the past 14 seasons. Written by Lincoln Zotarelli, Doug Gergela, Chad M. Hutchinson, David Dinkins, and Edsel Redden, and published by the UF Department of Horticultural Sciences, August 2013. http://edis.ifas.ufl.edu/hs323